Integrating AI Chatbots and Blockchain Smart Contracts: Enhancing Fintech Accessibility for Low-Digital-Literacy Workers: Author's Country: Indonesia - Ade Andri Hendriadi (Information System; Universitas Buana Perjuangan Karawang, 2026)
Digital financial services powered by artificial intelligence (AI) and blockchain technology present transformative opportunities for workforce empowerment, yet vocational workers with limited digital literacy face significant adoption barriers. This study develops and validates an integrated framework combining AI-powered chatbots with blockchain-based smart contracts to enhance fintech accessibility for low-digital-literacy workers in Indonesia. Using sequential explanatory mixed-methods design, we analyzed data from 618 vocational workers across five Indonesian cities through structural equation modeling (SEM) and 12 focus group discussions with 86 participants. Results demonstrate that AI chatbot personalization (β=0.726, p<0.001) and smart contract automation (β=0.742, p<0.001) significantly enhance adoption, with the integrated model explaining 71.4% of adoption variance. AI chatbots reduce onboarding time by 67% through adaptive interfaces and contextual guidance, while smart contracts enable automated salary disbursement (85% efficiency gain), micro-lending decisions (72% approval accuracy), and transparent credential verification (94% accuracy). Individual digital capability (β=0.721), organizational infrastructure (β=0.586), and technical barrier mitigation (β=-0.445) emerged as critical determinants. Qualitative findings reveal three transformation pathways: automated financial processes, personalized learning journeys, and trustless verification systems. The framework provides evidence-based guidance for practitioners and policymakers implementing inclusive fintech systems that combine AI’s adaptive learning capabilities with blockchain’s transparency and automation benefits.